Assessment of nutritional contents of different parts of moringa plant from selected districts of Oromia, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2024)
Moringa plants are among high-value trees and belong to the Moringaceae family, consisting of 13 species and highly distributed in Africa and southern Asia. It is multi-purpose tree with medicinal, nutritional, industrial and socio-economic values. Preliminary information indicates that the human dietary usage of the edible parts of these species is limited. Assessment of the nutritional quality of different moringa parts was not well documented in Oromia. Hence, the aim of this activity is to assess the nutritional qualities of different parts of moringa collected from different districts of Oromia. Sample collection was done from Bako from West Showa, Bishoftu from East Showa, Dalo Mena and Goro from Bale Zone, of Oromia representing mid and low land agro-ecologies of the region. Three to four sampling PAs were used from each district. Different parts of Moringa, namely, leaf, pod, bark, seed and flower were collected from the four districts at least in triplicate. The collected samples were made to dry at room temperature, milled with coffee miller, and passed through a 1 mm standard sieve. The prepared samples were analyzed for proximate and mineral compositions using standard methodologies. The result obtained indicated that leaf is rich in nutrients Ca, Na, Mn and Zn. Moringa flower is rich in nutrients like Zn and Mn, and second in K composition next to pod. The pod is also rich in K and Zn, while the fat and CP contents are high in the seed part of moringa. Generally, Higher % CP, K and P were found from the Bishoftu collection, while Mg, Ca and K were higher for the collection from DM. Bark is poor in protein content compared to other parts of the plant. However, Ca, Mg and Zn are double the optimum  composition of plant material. Finally, it is possible to use different moringa parts for food fortification, where determination for antioxidant and nutritional composition analysis is mandatory, as well as future research directions.Int. J. Agril. Res. Innov. Tech. 14(1): 62-69, June 2024